Synthesis and Characterization of Cyclopropaosmanaphthalenes Containing a Fused σ‐Aromatic Metallacyclopropene Unit. Issue 27 (22nd May 2019) - Chu, Zhenwei; He, Guomei; Cheng, Xiaoli; Deng, Zhirong; Chen, Jiangxi
Abstract: Metalla‐aromatics are important complexes that show unique properties owing to their highly conjugated systems, which show Hückel or Möbius aromaticity. Recently, several metalla‐aromatics showing spiro‐aromaticity or σ‐aromaticity have been reported. Herein, we report the isolation of the first cyclopropametallanaphthalenes, in which the metallacyclopropene ring shows σ‐aromaticity and weak hyperconjugative aromaticity. The reaction of OsCl2 (PPh3 )3 with o ‐ethynylphenyl alkynes in the presence of PPh3 followed by protonation with HCl yielded the first cyclopropametallanaphthalenes. The reaction mechanism and the aromaticity were also investigated by density functional theory studies. Abstract : The first cyclopropametallanaphthalene has been isolated from the reaction of OsCl2 (PPh3 )3 with an o ‐ethynylphenyl alkyne in the presence of PPh3 followed by protonation with HCl. The aromaticity of this cyclopropametallanaphthalene was studied through density functional theory calculations, confirming the σ‐aromaticity and weak hyperconjugative aromaticity in its fused unsaturated metallacyclopropene unit.